APLIKASI MIKROBA LIGNOSELULOLITIK INDIGENUS ASAL TANAH GAMBUT RIAU DALAM PEMBUATAN KOMPOS DARI CAMPURAN TANDAN KOSONG DAN LIMBAH CAIR PABRIK KELAPA SAWIT (Elaeis guineensis Jacq.) - Happy Zatul Munawarah; Delita Zul; Bernadeta Leni Fibriarti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Activity of palm oil industries usually has side result such as empty fruit bunch (EFB) and palm oil mill effluent (POME) wastes. Those wastes still contain organic material that can be utilized as a substrate for compost production. Because of lignin and cellulose components, composting of EFB takes about 60 days to obtain standardized composts. It is known that composting process can be shorterned by adding bioactivators. The purpose of this research was to analyze the ability of indigenous lignocellulolytic microbes isolated from peat soil in Riau as bioactivator in composting of EFB enriched by POME. The selected isolates consisting of 4 bacteria (BB_S27, BB_HP42, BB_HP41 and BB_K20) and 2 fungi (LIJ1 and L1J2) were subcultured on Nutrient Broth and Potato Dextrose Broth. Starters were then made from a combination of the isolates and fermented during 7 days using seedling media. The compost treatments included negative control (seedling media without isolates), positive control by using effective microorganisms (EM) and bioactivator made in USA, and 4 combinations of those isolates resulting 7 treatments. Composting was done by the windrow composting system utilizing 400 kg EFB as a substrate and inoculated by 50 liters of the starters at the 1st and 14th incubation time. During 35 days composting process, the substrate was enriched by 20 liters POME every 2 days. The best quality compost was produced by treatment K3 (a combination of 4 bacteria and 2 fungi) as its characters almost in line with the National Quality Standard (ISO) such as N 2.22%, C/N ratio 14.5, P 0.760%, K 3.44%, blackish brown color, smell like soil and unraveled texture. The highest celullolytic and ligninolytic microbes cell number were also found in compost treated by K3 with value 8.8 x 108 CFU/g and 1.2 X 109 CFU/g, respectively.